Electrochemical oxidation corrosion prevention method for aluminum-plated magnetic steel surface
By forming a composite structure of NdFeB oxide layer, aluminum layer and aluminum oxide layer on NdFeB permanent magnet material, the performance degradation of existing NdFeB magnets in corrosion environments is solved, and the effect of significantly improving the corrosion resistance of magnets is achieved.
Patent Information
- Application Number
- CN202411905498.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
AI Technical Summary
The existing neodymium iron boron permanent magnet materials are easily corroded when in contact with air and moisture, resulting in changes in performance. The existing vacuum aluminum plating methods have problems such as poor film quality, low density and poor corrosion resistance.
The composite structure is adopted, including neodymium iron boron oxide layer, aluminum layer and aluminum oxide layer, and a multi-layer structure is formed by combining high-temperature oxidation treatment and vacuum aluminum plating to improve the corrosion resistance of the magnet.
It significantly improves the corrosion resistance of magnets, enhances the density and adhesion of the coating, and is suitable for NdFeB parts of different thicknesses and shapes.
Smart Images

Figure CN119742145A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of surface treatment of NdFeB permanent magnet materials, and relates to a method for electrochemical oxidation corrosion protection on the surface of aluminum-plated magnetic steel, which mainly forms a conformal inert aluminum oxide layer on the surface of the aluminum-plated magnetic steel, thereby forming a multilayer structure of NdFeB oxide layer-Al layer-Al2O3 layer to improve its corrosion resistance. Background Art
[0002] In recent years, the market demand and industrial scale of sintered NdFeB permanent magnet materials are developing rapidly, and its application fields cover many industries such as modern home appliances, industrial motors, microelectronic motors, and new energy vehicles. However, there are still certain disadvantages in its application. For example, these magnetic materials are easily corroded in the process of contact with air and water, which causes changes in their performance. Therefore, surface treatment of NdFeB permanent magnet materials is essential.
[0003] The methods for surface treatment of NdFeB magnets mainly include electroplating, spraying, vacuum coating and passivation. With the explosive increase of new energy vehicles, NdFeB magnets have entered a new stage of development and growth. As an environmentally friendly technology, physical vapor deposition has many excellent characteristics that other surface treatment methods do not have. For example, by controlling its process parameters, a coating with fine grains, uniform thickness and excellent film / substrate bonding can be obtained. Although the vacuum aluminum plating method in the physical vapor deposition method has a fast film forming speed, it has defects such as poor film quality, low density and poor corrosion resistance, which limits its application development. Summary of the invention
[0004] In order to improve the above technical problems, the present invention provides a composite structure, including a NdFeB oxide layer, an aluminum layer and an aluminum oxide layer, wherein the aluminum layer is between the NdFeB oxide layer and the aluminum oxide layer.
[0005] According to an embodiment of the present invention, the thickness of the NdFeB oxide layer is 0.05-0.15 μm; preferably, the mass percentage of oxygen in the NdFeB oxide layer is 15-25%.
[0006] In the present invention, the mass percentage of oxygen can be tested by transmission electron microscope energy spectrum.
[0007] According to an embodiment of the present invention, the thickness of the aluminum layer may be 1.0 to 15.0 μm.
[0008] According to an embodiment of the present invention, the thickness of the aluminum oxide layer is 1.0-3.0 μm; preferably, the mass percentage of oxygen in the aluminum oxide layer is 40-47%.
[0009] According to an embodiment of the present invention, the total thickness of the aluminum layer and the aluminum oxide layer is 2.00-18.0 μm.
[0010] According to an embodiment of the present invention, the NdFeB oxide layer is prepared by cleaning and oxidizing the magnet body. For example, the magnet body is subjected to surface treatments such as degreasing, polishing and rust removal in sequence, and the treated magnet body is subjected to oxidation treatment to obtain the NdFeB oxide layer on the surface of the magnet body.
[0011] In one embodiment of the present invention, the oxidation treatment is performed by heating the magnet body after surface treatment at 200-400° C. in air atmosphere, and the heating temperature is 360° C. The oxidation treatment time is 5-40 minutes, and 30 minutes is exemplified.
[0012] According to an embodiment of the present invention, the aluminum layer is prepared by vacuum aluminum plating. For example, the vacuum aluminum plating method includes vacuum ion aluminum plating, vacuum aluminum evaporation, and the like.
[0013] In one embodiment of the present invention, the vacuum aluminum plating method comprises vacuum aluminum plating the magnet body after oxidation treatment using a vacuum coating device, and evacuating the vacuum chamber to 4.0x10 -3 Pa, firstly, the multi-arc ion with a plasma current of 1.0±0.2A was used to clean and activate the surface of the magnetic steel in an atmosphere with an argon flow rate of 500±50mL / min;
[0014] In one embodiment of the present invention, the vacuum ion aluminum plating can be vacuum ion barrel aluminum plating and / or vacuum ion rack aluminum plating. Exemplarily, the thickness of the aluminum layer obtained by vacuum ion barrel aluminum plating is 1.0-3.0 μm; the thickness of the aluminum layer obtained by vacuum ion rack aluminum plating is 1.0-10.0 μm.
[0015] In one embodiment of the present invention, before the aluminum layer is prepared by vacuum aluminum plating, the surface of the NdFeB oxide layer is cleaned and activated by multi-arc ions. For example, the surface of the magnetic steel is cleaned and activated by multi-arc ions with a plasma current of 1.0±0.2A in an atmosphere with an argon flow rate of 500±50mL / min. For another example, the activation time is 10 to 30 minutes.
[0016] According to an embodiment of the present invention, the aluminum oxide layer is formed by electrochemically anodizing the magnet body having the aluminum layer to form the aluminum oxide layer on the surface of the aluminum layer. Preferably, the electrolyte used in the electrochemical anodization is an acidic aqueous solution.
[0017] In one embodiment of the present invention, the electrochemical anodization is carried out in an electrolyte equipped with a constant temperature condition; for example, the constant temperature is 5 to 30°C.
[0018] In one embodiment of the present invention, the electrochemical anodization process is a constant voltage DC drive. For example, the voltage between the cathode and the anode is 10V to 100V, exemplarily 20V. Preferably, the current density during the electrochemical anodization process is 1 mA / cm 2 ~10mA / cm 2 , exemplified by 4 mA / cm 2 ; The electrochemical anodization time is 0.5 hours to 2 hours, and 1 hour is an example.
[0019] In one embodiment of the present invention, the acidic aqueous solution may be one or a mixture of two or more of sulfuric acid, phosphoric acid and oxalic acid. For example, the volume concentration of sulfuric acid in the acidic aqueous solution is 30-120 mL / L, exemplarily 80 ml / L; the concentration of phosphoric acid is 3-15 g / L, exemplarily 6 g / L; the concentration of oxalic acid is 3-15 g / L, exemplarily 7.5 g / L.
[0020] The present invention also provides a magnet, comprising a magnet body and the composite structure attached to the magnet body, wherein the NdFeB oxide layer in the composite structure is in contact with the magnet body.
[0021] According to an embodiment of the present invention, the magnet body is, for example, selected from neodymium iron boron ReFeBM magnetic steel, wherein:
[0022] Re is selected from at least one of Sm, La, Ce, Y, Nd, Pr, Ho, Gd, Dy and Tb, and the mass content of Re is 28wt% to 35wt%;
[0023] M is selected from at least one of Co, Ga, Cu, Al, Nb, Zr and Ti, and the mass content of M is 0.5wt% to 5wt%;
[0024] The mass content of B is 0.95wt% to 1.3wt%;
[0025] The rest is Fe and inevitable impurity elements.
[0026] For example, the composition of the magnet body is: Re mass content is 31.00% (including: Nd mass content is 24.00%, Pr mass content is 6.50%, Dy mass content is 0.50%), Fe mass content is 66.15%, Co mass content is 1.00%, Cu mass content is 0.13%, Ga mass content is 0.10%, Al mass content is 0.50%, Zr mass content is 0.04%, Ti mass content is 0.10%, B mass content is 0.98%. For example, the NdFeB ReFeBM magnet is 45H.
[0027] The present invention also provides a method for preparing the above-mentioned magnet, which comprises preparing the above-mentioned composite structure on the surface of the magnet body.
[0028] According to an embodiment of the present invention, the method for preparing the magnet comprises: sequentially cleaning and oxidizing the magnet body, vacuum aluminum plating, and electrochemical anodizing to sequentially form a neodymium iron boron oxide layer, an aluminum layer, and an aluminum oxide layer on the magnet body.
[0029] According to an embodiment of the present invention, the method for preparing the magnet comprises the following steps:
[0030] 1) Cleaning and oxidation treatment: The surface of the magnet body is subjected to degreasing, polishing and rust removal treatment in sequence, and the treated magnet body is subjected to oxidation treatment to form a NdFeB oxide layer on the surface of the magnet body;
[0031] 2) Vacuum aluminum plating: using multi-arc ion to clean and activate the surface of the magnet body treated in step (1) (10 to 30 minutes), and then vacuum aluminum plating (for example, using ion plating to heat the magnet body with a NdFeB oxide layer formed on the surface to a surface temperature of 150 to 250° C.) to form an aluminum layer on the surface of the NdFeB oxide layer;
[0032] 3) Electrochemical anodization: The magnet body prepared as above is placed in an acidic aqueous solution, and a dense aluminum oxide layer (Al2O3 layer) is formed on the surface of the aluminum layer by electrochemical anodization (using a platinum wire electrode with a diameter of 1 mm).
[0033] The present invention also provides application of the above oxide layer and / or aluminum layer and / or aluminum oxide layer in corrosion protection of magnets.
[0034] The present invention also provides the use of the above aluminum oxide layer in electrochemical oxidation corrosion protection on the surface of aluminum-plated magnetic steel.
[0035] The present invention also provides a method for improving the corrosion resistance of a magnet, comprising sequentially stacking the oxide layer, the aluminum layer and the aluminum oxide layer on the magnet body.
[0036] The present invention also provides a method for electrochemical oxidation corrosion protection on the surface of aluminum-plated magnetic steel, comprising forming the aluminum oxide layer on the surface of the aluminum-plated magnetic steel by electrochemical anodizing.
[0037] The present invention also provides applications of the magnet in modern household appliances, industrial motors, microelectronic motors, new energy vehicles, etc.
[0038] The present invention also provides a motor, which contains the above magnet or is prepared from the above magnet.
[0039] Beneficial effects of the present invention:
[0040] The present invention aims at the shortcomings of vacuum aluminum plating on the surface of existing magnetic steel, and provides a NdFeB magnet having a composite structure of NdFeB oxide layer-aluminum layer-aluminum oxide and a preparation method thereof. Through the synergistic effect of the composite structure, the density of the coating is increased, and the corrosion resistance of the magnet can be significantly improved while maintaining the adhesion of the coating to meet the requirements.
[0041] The present invention adopts high temperature oxidation to replace pickling passivation, and is used for vacuum aluminum plating pretreatment of NdFeB magnet steel, which can not only eliminate the surface stress of NdFeB substrate to make its surface layer fully oxidized, but also improve the density of NdFeB surface and enhance its corrosion resistance. At the same time, no organic substance or passivation film is introduced in the high temperature oxidation pretreatment process, thereby avoiding the organic substance or passivation film in the passivation layer on the surface of NdFeB substrate decomposition due to high temperature during vacuum aluminum plating, resulting in impurity enrichment between the surface of NdFeB substrate and aluminum layer, resulting in poor bonding between the two. And after vacuum aluminum plating, by placing the aluminum layer in an acidic aqueous electrolyte system through electrochemical anodization method, a certain thickness of aluminum oxide layer is prepared on the surface of the aluminum layer, which unexpectedly improves the corrosion resistance of the magnet. The anti-corrosion method of the present invention can be applied to NdFeB parts with Al layers of different thicknesses and different shapes, so as to further form a conformal inert aluminum oxide layer on the surface Al layer, thereby forming a NdFeB oxide-Al-Al2O3 multilayer structure on the magnet, so as to improve the anti-corrosion performance of the NdFeB parts with the Al layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 (a) is the structural surface of the sintered NdFeB magnet having a NdFeB oxide layer and an Al layer obtained after vacuum aluminum plating in step 2 of Example 1; Figure 1 (b) is the structural surface of the sintered NdFeB magnet having a multilayer structure of NdFeB oxide layer, Al layer and Al2O3 layer obtained after electrochemical anodization in step 3 of Example 1.
[0043] Figure 2The present invention is a schematic structural diagram of a sintered NdFeB magnet having a multilayer structure of NdFeB oxide layer, Al layer and Al2O3 layer; in the figure: 1, NdFeB magnet; 2, NdFeB oxide layer; 3, Al layer; 4, Al2O3 layer. DETAILED DESCRIPTION
[0044] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0045] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0046] The sulfuric acid used in the following examples of the present invention is 98% concentrated sulfuric acid with a density of 1.84 g / mL. For example, a volume concentration of 80 mL / L sulfuric acid means dissolving 80 mL of 98% concentrated sulfuric acid in 1 L of water.
[0047] Example 1
[0048] A method for preparing a magnet comprises the following steps:
[0049] 1. Cleaning and oxidation treatment: Degrease the tested NdFeB magnet in an alkaline degreasing agent, wash with water and dry it. Polish the magnet with nylon diamond composite abrasive, with the mass ratio of abrasive to magnet being 2:1. Ultrasonic deashing is performed with a weak acid deashing agent, with a deashing agent concentration of 6%. After deashing, the magnet is rinsed with pure water and ultrasonically cleaned for 2 minutes. After drying, the magnet is baked at 360°C for 30 minutes.
[0050] The alkaline degreasing agent is Henkel 212 reagent, and the weak acid deashing agent is Aluminum Source L-601 reagent.
[0051] 2. Vacuum aluminum plating: vacuum aluminum plating is performed on the NdFeB magnet after cleaning and oxidation treatment using vacuum coating equipment, and the vacuum chamber is evacuated to 4.0x10 -3 Pa, first use plasma current 1.0±0.2A multi-arc ion, in an atmosphere of argon flow rate 500±50mL / min, clean and activate the magnetic steel surface for 30 minutes, vacuum ion barrel aluminum plating time is 30 minutes, keep the coating chamber temperature at 160℃, and then maintain the coating chamber under vacuum cooling for 40 minutes to room temperature;
[0052] 3. Electrochemical anodization: The vacuum aluminum-plated magnetic steel is used as the anode, and the 1mm platinum wire electrode is used as the cathode. The constant voltage DC drive is adopted, and the cathode and cathode voltage is 20V. The electrolyte for electrochemical anodization is an acidic aqueous solution with a volume concentration of 80mL / L sulfuric acid and 7.5g / L oxalic acid. The current density is 4mA / cm 2 , anodization time 1 hour, to obtain Example product 1.
[0053] Example 2
[0054] A method for preparing a magnet, compared with Example 1, the only difference is that: step 2 vacuum aluminum plating is: vacuum ion aluminum plating time is 30 minutes, and other conditions are the same as Example 1, to obtain Example product 2.
[0055] Example 3
[0056] A method for preparing a magnet comprises the following steps:
[0057] 1. Cleaning and oxidation treatment: Degrease the tested NdFeB magnet in an alkaline degreasing agent, wash with water and dry it. Polish the magnet with nylon diamond composite abrasive, with the mass ratio of abrasive to magnet being 2:1. Ultrasonic deashing is performed with a weak acid deashing agent, with the concentration of the deashing agent being 6%. After deashing, the magnet is rinsed with pure water and ultrasonically cleaned for 2 minutes. After drying, the magnet is baked at 390°C for 20 minutes.
[0058] 2. Vacuum aluminum plating: the conditions are the same as those in Example 1;
[0059] 3. Electrochemical anodization: The vacuum aluminum-plated magnetic steel is used as the anode, and the 1mm platinum wire electrode is used as the cathode. The constant voltage DC drive is adopted, and the cathode and cathode voltage is 25V. The electrolyte for electrochemical anodization is an acidic aqueous solution with a volume concentration of 80mL / L sulfuric acid and 6g / L phosphoric acid. The current density is 3mA / cm at a constant temperature of 25℃. 2 , anodization time 1.5 hours, to obtain Example product 3.
[0060] Example 4
[0061] A method for preparing a magnet comprises the following steps:
[0062] 1. Cleaning and oxidation treatment: the conditions are the same as those in Example 3;
[0063] 2. Vacuum aluminum plating: the conditions are the same as those in Example 2;
[0064] 3. Electrochemical anodization: The conditions are the same as those in Example 3 to obtain Example Product 4.
[0065] Comparative Example 1
[0066] A method for preparing a magnet comprises the following steps:
[0067] 1. Cleaning treatment: Degrease the tested 45H / 40*20*4mm NdFeB magnet in an alkaline degreasing agent, wash with water and dry, polish with nylon diamond composite abrasive, the mass ratio of abrasive to magnet is 2:1, then use weak acid deashing agent to ultrasonically deash at room temperature, the concentration of deashing agent is 6%, rinse the deashed magnet with pure water, use iron-based passivation liquid, passivate at room temperature for 15s, rinse with pure water, soak in 65℃ hot water for 30s, and bake at 120℃ for 15min;
[0068] 2. Vacuum aluminum plating: vacuum aluminum plating is performed on the cleaned NdFeB magnets using vacuum coating equipment, and the vacuum chamber is evacuated to 4.0x10 -3 Pa, first use multi-arc ion to clean and activate the magnetic steel surface for 30 minutes, vacuum ion hang-plating aluminum for 30 minutes, and then maintain the coating chamber under vacuum cooling for 40 minutes;
[0069] 3. Passivation treatment: The vacuum aluminum-plated NdFeB magnet is sandblasted with glass beads using sandblasting equipment, with a spray gun pressure of 1.0kg / cm 2 , sandblasting for 400s, using 200±10mL / L aluminum and aluminum alloy trivalent chromium passivation solution, passivation for 120s at 35℃, blow-drying the passivated product, and drying at 60℃ for 15min to obtain comparative example product 1.
[0070] Among them: the iron-based passivation liquid uses Guangzhou Kaimeng ID3000-1 reagent, and the aluminum and aluminum alloy trivalent chromium passivation liquid uses Suzhou Passivation New Materials DH605 reagent.
[0071] Comparative Example 2
[0072] A method for preparing a magnet comprises the following steps:
[0073] 1. Cleaning treatment: the conditions are the same as those in Comparative Example 1;
[0074] 2. Vacuum aluminum plating: vacuum aluminum plating is performed on the NdFeB magnet after cleaning and oxidation treatment using vacuum coating equipment, and the vacuum chamber is evacuated to 4.0x10 -3 Pa, first use multi-arc ion to clean and activate the magnetic steel surface for 30 minutes, vacuum ion barrel aluminum plating time is 30 minutes, and then maintain the coating chamber under vacuum cooling for 40 minutes;
[0075] 3. Passivation treatment: The conditions are the same as those of comparative example 1 to obtain comparative example product 2.
[0076] Comparative Example 3
[0077] A method for preparing a magnet comprises the following steps:
[0078] 1. Cleaning treatment: Degrease the tested NdFeB magnet in an alkaline degreasing agent, wash with water and dry it. Polish the magnet with nylon diamond composite abrasive, with the mass ratio of abrasive to magnet being 2:1. Ultrasonic deashing is performed with a weak acid deashing agent, with a deashing agent concentration of 6%. After deashing, the magnet is rinsed with pure water and ultrasonically cleaned for 2 minutes. After drying, the magnet is baked at 360°C for 30 minutes.
[0079] 2. Vacuum aluminum plating: the conditions are the same as those in Comparative Example 1;
[0080] 3. Passivation treatment: The conditions are the same as those of comparative example 1 to obtain comparative example product 3.
[0081] Comparative Example 4
[0082] A method for preparing a magnet comprises the following steps:
[0083] 2. Cleaning treatment: the conditions are the same as those in Comparative Example 1;
[0084] 3. Vacuum aluminum plating: the conditions are the same as those in Comparative Example 1;
[0085] 4. Electrochemical anodization: The vacuum aluminum-plated magnetic steel is used as the anode, and the 1mm platinum wire electrode is used as the cathode. The constant voltage DC drive is adopted, and the cathode and cathode voltage is 25V. The electrolyte for electrochemical anodization is an acidic aqueous solution of 80mL / L sulfuric acid and 6g / L phosphoric acid. The current density is 3mA / cm at a constant temperature of 25℃. 2 , anodization time 1.5 hours, to obtain comparative example product 4.
[0086] Comparative Example 5
[0087] A method for preparing a magnet comprises the following steps:
[0088] 1. Cleaning treatment: the conditions are the same as those in Comparative Example 1;
[0089] 2. Vacuum aluminum plating: the conditions are the same as those in Comparative Example 1;
[0090] 3. Oxidation treatment: Store at room temperature for more than 24 hours, and fully oxidize the surface to obtain comparative example product 5.
[0091] Comparative Example 6
[0092] A method for preparing a magnet comprises the following steps:
[0093] 1. Cleaning treatment: the conditions are the same as those in Comparative Example 2;
[0094] 2. Vacuum aluminum plating: the conditions are the same as those in Comparative Example 1;
[0095] 3. Oxidation treatment: Store at room temperature for more than 24 hours, and the surface is fully oxidized to obtain comparative example product 6.
[0096] The adhesion and corrosion resistance of the magnets obtained in Examples 1-4 and Comparative Examples 1-6 were measured, and the results are shown in Table 1 below.
[0097] The test method is as follows:
[0098] Shear strength: The criterion for judging the bonding strength between a coating and a substrate, i.e. the ability of the coating bonding strength to resist damage under shear.
[0099] SST: Under neutral conditions, spray a 5% sodium chloride solution at 35°C on the product surface in a mist form.
[0100] PCT: High temperature and high pressure cooking test at 2 standard atmospheres and 100% humidity.
[0101] Table 1
[0102]
[0103] The above results show that the present invention adopts high-temperature oxidation instead of pickling passivation for vacuum aluminum plating pretreatment, which can not only eliminate the surface stress of the NdFeB substrate, but also fully oxidize its surface layer to improve the surface density, thereby enhancing the corrosion resistance of the magnet. At the same time, no organic matter or passivation film is introduced in the high-temperature oxidation pretreatment process of the present invention, thereby avoiding the high-temperature decomposition of organic matter or passivation film in the passivation layer on the surface of the NdFeB substrate during vacuum aluminum plating, resulting in the enrichment of impurities between the surface of the NdFeB substrate and the aluminum layer, resulting in the deterioration of the bonding force between the two. After vacuum aluminum plating, by placing the aluminum layer in an acidic aqueous electrolyte system and using an electrochemical anodizing method to prepare an aluminum oxide layer of a certain thickness on the surface of the aluminum layer, the corrosion resistance of the magnet is unexpectedly improved. The anti-corrosion method of the present invention can be applied to NdFeB parts with Al layers of different thicknesses and different shapes, so as to further form a conformal inert aluminum oxide layer on the surface Al layer, thereby forming a NdFeB oxide-Al-Al2O3 multilayer structure on the magnet, so as to improve the anti-corrosion performance of the NdFeB parts with the Al layer.
[0104] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A composite structure, characterized in that: The invention comprises a neodymium iron boron oxide layer, an aluminum layer and an aluminum oxide layer, wherein the aluminum layer is located between the neodymium iron boron oxide layer and the aluminum oxide layer.
2. The composite structure according to claim 1, characterized in that The thickness of the NdFeB oxide layer is 0.05-0.15 μm. Preferably, the aluminum layer may have a thickness of 1.0 to 15.0 μm. Preferably, the aluminum oxide layer has a thickness of 1.0 to 3.0 μm. Preferably, the total thickness of the aluminum layer and the aluminum oxide layer is 2.0-18.0 μm. Preferably, the NdFeB oxide layer is prepared by cleaning and oxidizing the magnet body. For example, the magnet body is subjected to surface treatments such as degreasing, polishing and rust removal, and then the treated magnet body is oxidized to obtain the NdFeB oxide layer on the surface of the magnet body. Preferably, the oxidation treatment is performed by heating the surface-treated magnet body at 200-400° C. in an air atmosphere. Preferably, the aluminum layer is prepared by vacuum aluminum plating. Preferably, the vacuum aluminum plating method includes vacuum ion aluminum rolling plating, vacuum ion aluminum hanging plating, vacuum evaporation and the like. Preferably, the aluminum oxide layer is formed by electrochemically anodizing the magnet body having the aluminum layer to form an aluminum oxide layer on the surface of the aluminum layer. Preferably, the electrolyte used in the electrochemical anodization is an acidic aqueous solution. Preferably, during the electrochemical anodic oxidation process, the voltage between the cathode and the anode is 10V to 100V; the current density is 1 mA / cm 2 ~10mA / cm 2 ; The electrochemical anodization time is 0.5 hours to 2 hours. Preferably, the acidic aqueous solution may be one or a mixture of two or more of sulfuric acid, phosphoric acid and oxalic acid. Preferably, the concentration of sulfuric acid in the acidic aqueous solution is 30-120 mL / L; the concentration of phosphoric acid is 3-15 g / L; and the concentration of oxalic acid is 3-15 g / L.
3. A magnet, characterized in that: It comprises a magnet body and the composite structure attached to the magnet body, wherein the NdFeB oxide layer in the composite structure contacts the magnet body.
4. The method for preparing a magnet according to claim 3, characterized in that: The preparation method comprises preparing the composite structure according to claim 1 or 2 on the surface of a magnet body.
5. The method for preparing a magnet according to claim 4, characterized in that: The following steps are involved: 1) Cleaning and oxidation treatment: The surface of the magnet body is subjected to degreasing, polishing and rust removal treatment in sequence, and the treated magnet body is subjected to oxidation treatment to form a NdFeB oxide layer on the surface of the magnet body; 2) Vacuum aluminum plating: using multi-arc ion to clean and activate the surface of the magnet body treated in step (1), and then vacuum aluminum plating to form an aluminum layer on the surface of the NdFeB oxide layer; 3) Electrochemical anodization: The magnet body prepared as above is placed in an acidic aqueous solution, and a dense aluminum oxide layer is formed on the surface of the aluminum layer through electrochemical anodization.
6. Use of the oxide layer and / or aluminum layer and / or aluminum oxide layer according to claim 1 or 2 in the corrosion protection of magnets.
7. Use of the aluminum oxide layer according to claim 1 or 2 in electrochemical oxidation corrosion protection of aluminum-plated magnetic steel surfaces.
8. A method for improving the corrosion resistance of a magnet, characterized in that: The method comprises sequentially stacking an oxide layer, an aluminum layer and an aluminum oxide layer as described in claim 1 or 2 on a magnet body.
9. A method for electrochemical oxidation corrosion protection of aluminum-plated magnetic steel surface, characterized in that: The method comprises forming the aluminum oxide layer as claimed in claim 1 or 2 on the surface of aluminum-plated magnetic steel by electrochemical anodizing.
10. A motor, characterized in that: It contains the magnet described in claim 3 or is prepared from the magnet described in claim 3.
Citation Information
Patent Citations
Preparation method for corrosion-resistant sintered neodymium iron boron permanent magnet with aluminum-based ceramic composite coating on surface
CN108754424A
In-situ composite coating used for protecting surface of neodymium-iron-boron magnet and preparation method of coating
CN109346306A
Clad layer, metal magnet with clad layer and preparation method for clad layer
CN112176286A
Sintered neodymium magnet, its manufacturing method and rotary machine
JP2005310975A
Highly corrosion-resistant r-t-b based rare earth magnet
JP2009099853A